Pengembangan Pariwisata Ekonomi Kreatif Terpadu Untuk Meningkatkan Daya Saing Daerah : Penelitian - Arum Rakhmasari Octivaningsih; Muhammad Sabir; Nurjanna Ladjin; Asminar Mokodongan; Andriya Risdwiyanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The development of integrated creative economy tourism is a crucial need for regions to increase their competitiveness. Activities are implemented through preparation and planning, surveys and data collection, program implementation, monitoring and evaluation, and dissemination and sustainability. The results of these activities indicate that creative economy-based tourism development has significant potential to drive regional economic growth and increase regional competitiveness, through the utilization of local culture, traditional wisdom, and unique natural potential. The creative economy strengthens the tourism sector through innovative local products, thereby expanding markets and strengthening cultural identity. The implementation of creative tourism creates interactive experiences for tourists while opening up spaces for local creativity. Digital transformation is also key to modern and efficient destination promotion and management, in line with global trends in technology-based tourism. Thus, the development of integrated creative economy tourism can be a sustainable strategy to strengthen regional competitiveness in the era of globalization.